Age-related Changes in Computed Tomography Density of Thyroid Gland in Children: A Single-Center Retrospective Study in Northern China. Issue 1 (January 2022) - Yi, Xiaoli; Zhao, Pengfei; Song, Qinwei; Yuan, Xinyu; Wang, Zhenchang
Abstract : Objective: The thyroid gland normally presents as a hyperdense organ on noncontrast computed tomography (CT) in adults. The correlation between thyroid gland CT density and its functional status has been studied; however, little is known regarding its density in children with normal thyroid functions. We aimed to assess the correlation between thyroid gland CT density and age in children with normal thyroid functions. Methods: From April 2017 to March 2021, we enrolled 74 patients who had normal thyroid functions within 1 month before or after undergoing neck or cervical spine CT for trauma, neck masses, congenital diseases, and airway stenosis. Their CT images were retrospectively analyzed by 2 independent radiologists. Based on age, patients were divided into 4 groups: infant, preschool-aged, school-aged, and adolescence groups. Results: Patients with thyroid gland hypodensity in the infant group (70%, 14 of 20) were significantly more numerous than those in preschool-aged (25%, 4 of 16), school-aged (20%, 5 of 25), and adolescence (15.4%, 2 of 13) groups ( P = 0.007, 0.001, and 0.002, respectively, Fisher exact test). The mean CT density of the thyroid gland was also lower in the infant group compared with the densities in other age groups. There was a weak positive correlation between thyroid CT density and age ( r = 0.264, P = 0.023, linear regression analysis). Conclusions: Thyroid CT density is related to age in children. The thyroid gland normally has a low density on noncontrast CT in most infants with normal thyroid function.